Fruits /. - Aoki, Shoich (Phaidon, 2001)
Fruits is a collection of Tokyo street fashion portraits from Japan's premier street fanzine of the same title. The 300 portraits of teenagers represent a unique documentation of the changing face of street fashion throughout the last decade.